Halal Tourism Promotion in Indonesia: An Analysis on Official Destination Websites - Suradin, Muhammad (Journal of Indonesian Tourism and Development Studies, 2018)
Nowadays, Halal tourism has become a popular form of tourism which attracting many countries to capitalize on the Muslim market. However, because of the Islamic law, targeting this market segment may not be the same as targeting the mundane tourism segment. Hence, a cohort of studies suggests that the internet could be a solution to reach this specific tourism market. Furthermore, some studies also suggest that to influence Muslim tourism destination choice, tourism destination organizations should use Islamic Attributes of Destination in their promotion campaigns. This is also the case of Indonesia as the world's biggest Muslim country, which is trying to attract Muslim tourists visit. Nevertheless, the existing studies on halal tourism promotion in Indonesia are still scarce. Adopting the qualitative form of content analysis, this research tries to add to the scant studies on halal tourism destination promotion in Indonesia by examining the content in official websites of DMOs according to the Indonesia's national plan on Halal tourism. Keywords: Halal Tourism, Islamic Attributes of Destination, Destination Management Organization, Websites.